Impact of Cardiovascular Diseases on Endodontic Treatment: An Integrative Review of Risk Factors - Rebecca Marinho-Siqueira; José Evando da Silva-Filho; Emanuelle dos Santos Beserra; Bruno Carvalho de Vasconcelos; Bernardo Almeida Aguiar; Alinne Patierry Oliveira Pacífico Feitosa (Archives of Current Research International, 2025)
Introduction: The current knowledge of cardiovascular diseases highlights the need for a deeper understanding of the association between endodontic infections and cardiovascular risk. Considering the potential relationship between cardiovascular risk factors and oral conditions, it is essential to establish guidelines that support an integrated approach to oral and systemic health. Aim: To analyze through an integrative review the influence of cardiovascular diseases on endodontic treatment and their main associated risk factors. Materials and Methods: A comprehensive search was conducted in the PubMed, Google Scholar, and Virtual Health Library databases using the English descriptors: inflammation, cardiovascular diseases, and root canal. Filters were applied for language (Portuguese and English), full-text availability, and publication date between 2019 and 2024. Initially, 17,774 references were identified. After applying the eligibility criteria and selecting by title, abstract, and full-text reading, 8 articles were included in the review. Results: Periapical lesions, root-filled teeth, and tooth loss were associated with myocardial infarction. Comorbidities such as diabetes, hypertension, dyslipidemia, and smoking exacerbated oral-systemic interactions. Endodontic infections were linked to systemic inflammation, with elevated expression of hs-CRP, IL-1β, ADMA, ET-1, and MMP-2. Discussion: The findings reinforce the importance of integrating oral and systemic health, especially in patients with cardiovascular predisposition. Identifying risk factors and controlling oral inflammation may contribute to improved clinical outcomes. Conclusion: Proper endodontic therapy offers both local and systemic benefits, serving as a relevant resource in the prevention of cardiovascular complications associated with oral infections.